Long- and Short-term Effects of Corticosteroids on the Rate of Orthodontic Tooth Movement and Associated Histological Changes in Animal Model: A Systematic Review - Ashish Agrawal; Aparajita Pandey (Journal of Clinical and Diagnostic Research)
Introduction: Orthodontic Tooth Movement (OTM) involves a multifaceted process intricately linked to the remodelling of bone and tissue subsequent to the application of orthodontic forces on teeth. Various factors, such as age, gender, root morphology and the administration of medications like Corticosteroids (CS), can affect the remodelling of alveolar bone and the pace of OTM. The influence of CS on the rate of OTM has been reviewed in animal studies with conflicting results. Aim: To systematically investigate the effect of CS (duration) on the rate of OTM in animal models (rats). Materials and Methods: A sytematic review was conducted at the Department of Dentistry, Faculty of Dental Sciences, IMS BHU, Varanasi, Uttar Pradesh, India. A total of five databases (PubMed, Google Scholar, Wiley Library, Cochrane Library, Scopus) were searched without restrictions until March 5, 2024, using the following keywords: CS, orthodontic, tooth movement and bone remodelling. All in-vivo experimental animal studies assessing the rate of OTM following the administration of CS were included. The Systematic Review Centre for Laboratory Animal Experimentation (SYRCLE) risk of bias tools were utilised. The reporting of the present review was based on the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) guidelines. The protocol was registered with the number CRD42024441077 in the Prospective Register of Systematic Reviews (PROSPERO) database (http://www.crd.york.ac.uk/PROSPERO). Results: The results of all five studies (all five studies being in-vivo experimental animal studies) concluded that CS causes suppression of osteoclastic activity histologically. The dosage and duration of steroids used in the studies showed a significant influence on the extent of OTM. Nevertheless, histological examinations revealed changes indicating suppression of osteoclastic activity, as evidenced by reduced activity of Tartrate Resistant Acid Phosphatase (TRAP), a major cytochemical marker of osteoclasts and a decrease in the length of root resorption. Conclusion: The CS induces alterations in the rate of tooth movement. However, intervention studies have concluded that the effect on OTM depends on both the dose and duration (≤3 weeks=short-term and ≥7 weeks=long-term) of administration.